SOCIO-PSYCHOLOGICAL MODEL OF FAMILY RELATIONS - Gaibova Nargiza Anorbaevna (American Journals Publishing, 2023)
The article scientifically analyses the socio-psychological model of family relations, typology, structure, forms of family, methods of upbringing, as well as issues of modern family problems. In addition to psychological literature, the article used pedagogical literature.
Keywords: Family, adolescent, sibling status, sibling relationship, conflict, eldest child, middle child, last child, only child, interpersonal relationships.